Isolated pleural aspergillosis: Case description and challenges in management. Issue 4 (2nd October 2017) - Ross, Bryan; Taha, Karim; Taggart, Linda R.; Blitz, Maurice; Anand, Anju
ABSTRACT: Aspergillus species are ubiquitous fungi in the environment. They are responsible for a wide variety of clinical syndromes including allergic manifestations, saprophytic colonization, and invasive disease, which can disseminate. Aspergillus fumigatus is the most common Aspergillus species to cause human infection, and the respiratory system is the primary portal of entry. Although pulmonary aspergillosis is well-characterized, pleural aspergillosis in the absence of pulmonary infection is rare and difficult to treat. The ubiquity of Aspergillus species in the environment underscores the importance of host factors in colonization and infection. We outline the case of a 73-year-old man who presented with dyspnea and constitutional symptoms. Following a thorough workup including systematic exclusion of more common entities, he was diagnosed with isolated pleural aspergillosis. In the absence of considerable supporting literature we discuss the diagnosis, clinical course and management challenges of this rare entity.